(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
In the healthcare sector data mining is becoming increasingly popular, because medicine organizations produce and collect large volumes of information day by day. Using data mining and data mining applications can help for each medicine organization and parts in the healthcare industry. For example, clients through data mining can take better services in healthcare, doctors better diagnose patients ’ diseases and evolve a course of treatment.Of course, in these examples not the full range of power of data mining in the medicine sector, but main ones. Therefore we have problems like how all this system, also data mining is processed in general and using intelligent data analysis in our country. The objective of this article is to show how the healthcare sector can benefit greatly from data mining and consider possible solution for problems, which described above.